2020
DOI: 10.1186/s12884-020-03300-4
|View full text |Cite
|
Sign up to set email alerts
|

Fetal double aortic arch: prenatal sonographic and postnatal computed tomography angiography features, associated abnormalities and clinical outcomes

Abstract: Background Fetal double aortic arch (DAA) malformation is a rare congenital heart disease with few reported cases in the literature. We aimed to investigate the characteristics of prenatal ultrasound and postnatal computed tomography angiography (CTA) of DAA and to describe the associated anomalies and clinical outcomes to improve prenatal diagnosis and assist in perinatal management. Methods The obstetric ultrasound imaging databases of seven tertiary referral centers were reviewed retrospectively to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
4
13
5
Order By: Relevance
“…In our study, 42.5% of patients were symptomatic, which is similar to the rate reported by Guo et al 3 and lower than that reported by Vigneswaran et al 9 (65%) and Trobo et al 14 (72.4%) (Table 4). Based on our findings and the available literature, we can conclude that symptoms occur in approximately 40-70% of patients with DAA.…”
Section: Outcomesupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, 42.5% of patients were symptomatic, which is similar to the rate reported by Guo et al 3 and lower than that reported by Vigneswaran et al 9 (65%) and Trobo et al 14 (72.4%) (Table 4). Based on our findings and the available literature, we can conclude that symptoms occur in approximately 40-70% of patients with DAA.…”
Section: Outcomesupporting
confidence: 88%
“…This is higher than the 41% intervention rate reported by Guo et al 3 and lower than the 87% rate reported by Vigneswaran et al 9 (Table 4). This may be explained by the fact that in the study of Guo et al 3 , none of the asymptomatic patients had significant tracheal or esophageal compression, while 13/47 (27.7%) patients in the study of Vigneswaran et al 9 were asymptomatic with an abnormal tracheal appearance. Furthermore, we did find a statistically significant relationship between the type of DAA and outcome.…”
Section: (41%)contrasting
confidence: 62%
“…10,11 In 1984, Marmon et al 10 Vascular ring is an extra-cardiac congenital abnormality and, as expected, heart function as evaluated by echocardiogram was normal for all the examined patients in both groups. Guo et al 22 evaluated 27 patients with double aortic arch up to a year following birth and found similar findings.…”
Section: Resultsmentioning
confidence: 65%
“…DAA is the most common cause of tracheal and esophageal compression of aortic origin [ 43 ]. The rate of symptomatic neonates varies between 41% and 98% in different studies [ 34 , 44 ]. In our study group, only one case of isolated DAA was born alive and the neonate did not develop compression symptoms in the neonatal and early childhood period.…”
Section: ⧉ Discussionmentioning
confidence: 99%